DNA encoding schemes herald a new age in cybersecurity for safeguarding digital assets - Sehrish, Aqeel; Sajid Ullah, Khan; Adnan Shahid, Khan; Meshal, Alharbi; Sajid, Shah; Mohammed EL, Afendi; Naveed, Ahmad (Nature Portfolio, 2024)
With the urge to secure and protect digital assets, there is a need to emphasize the immediacy of taking measures to ensure robust security due to the enhancement of cyber security. Diferent advanced methods, like encryption schemes, are vulnerable to putting constraints on attacks. To encode the digital data and utilize the unique properties of DNA, like stability and durability, synthetic DNA sequences are ofered as a promising alternative by DNA encoding schemes. This study enlightens the exploration of DNA’s potential for encoding in evolving cyber security. Based on the systematic literature review, this paper provides a discussion on the challenges, pros, and directions for future work. We analyzed the current trends and new innovations in methodology, security attacks, the implementation of tools, and diferent metrics to measure. Various tools, such as Mathematica, MATLAB, NIST test suite, and Coludsim, were employed to evaluate the performance of the proposed method and obtain results. By identifying the strengths and limitations of proposed methods, the study highlights research challenges and ofers future scope for investigation.